Protecting who? Optimal social protection responses to shocks with limited information - Carlos Gustavo Ospino Hernandez; Jamele Rigolini; Sarah Coll-Black; Ana María Oviedo (Institute of Labor Economics (IZA), 2023)
The literature on shock-responsive social protection focuses on operational features that improve the speed and reach of the response, but little is known about the optimal design of emergency social protection responses in terms of which programs to use, information about the people affected, and the extent of their losses. This paper studies optimal social protection responses to shocks, using microsimulations of different social assistance responses in Albania, Moldova, and North Macedonia. The paper shows that optimal design depends not only on the magnitude of the shock, but also on how the shock affects welfare rankings and on the parameters of the existing social assistance system, including the generosity of the schemes and how well they cover the poor. For given budgets, a universal transfer remains a suboptimal response. However, the extent to which existing programs should be expanded, as designed, to additional beneficiaries depends on the type of shock. When a shock tends to affect households homogeneously, increasing generosity and expanding the existing targeted social assistance program using established welfare metrics to assess eligibility is an effective response. When shocks affect households heterogeneously and bring some of them into extreme poverty, then pre-shock welfare indicators carry little information and policy makers should provide support through a new program or modified eligibility criteria, according to information on who suffered the shock. This analysis points to the importance of planning in advance for future crises and, within this, considering the optimal design of emergency social protection responses.
Keywords: D6; H5; I3; Q5; 330; social protection; adaptive social protection; disaster risk management; COVID-19; targeting